The plot of D. N. Mamin-Sibiryak’s novel „Mountain nest“ - Galinienė, L. (Literatūra, 1969)
The author analyses in the present article the specific traits of the plot of Mamin-Sibiryak’s novel Mountain Nest (1884) notable for its being built up upon a real event witnessed by Mamin-Sibiryak in his childhood. The plot based on real events enables Mamin-Sibiryak to give up concentric composition and as a result to write a novel with a multitude of characters. The dynamic and smooth plot of the Mountain Nest, its conflictiveness heralded the development of Mamin-Sibiryak’s dramatic craft of the nineties.